2016
DOI: 10.1920/re.ifs.2016.0112
|View full text |Cite
|
Sign up to set email alerts
|

IFS Green Budget 2016

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In undertaking this research, we found that freely available and reliable forecasting data that would be informative in relation to alcohol-related hospital admissions were limited. Nevertheless, some relevant time-series, such as alcohol taxation [34] and ethnic population [35] trends and forecasts, are available. We plan to investigate the impact of adding these data to our now-and forecasting models.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In undertaking this research, we found that freely available and reliable forecasting data that would be informative in relation to alcohol-related hospital admissions were limited. Nevertheless, some relevant time-series, such as alcohol taxation [34] and ethnic population [35] trends and forecasts, are available. We plan to investigate the impact of adding these data to our now-and forecasting models.…”
Section: Strengths and Limitationsmentioning
confidence: 99%